2017
DOI: 10.1155/2017/4072658
|View full text |Cite
|
Sign up to set email alerts
|

Buyang Huanwu Decoction Ameliorates Poststroke Depression via Promoting Neurotrophic Pathway Mediated Neuroprotection and Neurogenesis

Abstract: Objective. The aim of the present research is to investigate the therapeutic effect of Buyang Huanwu Decoction (BHD) in poststroke depression (PSD) animal model and illustrate its underlying mechanism via promoting neurotrophic pathway mediated neuroprotection and neurogenesis. Methods. To induce PSD rat model, isolation housed rats that received middle cerebral artery occlusion (MCAO) surgery successively suffered from chronic mild stress (CMS) treatment for consecutive twenty-one days. Meanwhile, rats were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 47 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…Recent studies have demonstrated that the BDNF/ERK1/2/CREB signaling pathway in rodents is sufficient to elicit depression, and pharmaceutical drugs display antidepressant effects via this pathway ( Yi et al, 2014 ; Li et al, 2015 ; Luo et al, 2017 ). Conversely, there is a conflicting concept that BDNF is considered to be a downstream factor affected by CREB ( Shieh et al, 1998 ; Tao et al, 1998 ), and the ERK1/2/CREB/BDNF signaling pathway is involved in chronic mild stress ( Thome et al, 2000 ; Guo et al, 2014 ; Yan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the BDNF/ERK1/2/CREB signaling pathway in rodents is sufficient to elicit depression, and pharmaceutical drugs display antidepressant effects via this pathway ( Yi et al, 2014 ; Li et al, 2015 ; Luo et al, 2017 ). Conversely, there is a conflicting concept that BDNF is considered to be a downstream factor affected by CREB ( Shieh et al, 1998 ; Tao et al, 1998 ), and the ERK1/2/CREB/BDNF signaling pathway is involved in chronic mild stress ( Thome et al, 2000 ; Guo et al, 2014 ; Yan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that this pathway was inactivated in PSD rats after CUMS, which was also consistent with previous reports. [40][41][42] Furthermore, our study showed that GAA could activate the ERK/CREB pathway by increasing the phosphorylation of ERK and CREB. Additionally, the inhibition of this signaling using PD reversed GAAinduced M1/M2 microglial polarization, further suggesting GAA exerted its activity in PSD by regulating the ERK/CREB pathway.…”
Section: Discussionmentioning
confidence: 56%
“…Buyang Huanwu decoction (BYHWD), a classical TCM formula, is the most frequently used for treating stroke (40.32%) by far (Hung et al, 2015). Evidence shows BYHWD substantial neuroprotective and function-improving effects in animal models of focal cerebral ischemia and desirable clinical efficacy for both hemorrhagic and ischemic stroke (Guo et al, 2015;Luo et al, 2017;Pan et al, 2017). What's more, BYHWD improves long-term motor dysfunctions, swallowing difficulties, cognitive disorders, and dysarthria, which are tough to be effective by Western medicine (Zhang et al, 2016a;Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%